(untitled) (Jurnal Edukasi dan Penelitian Matematika, 2025)
Mathematics learning outcomes are crucial for calculating student progress in achieving learning objectives. Grade VIII at SMPN 7 Padang is no exception to this low achievement. Inappropriate learning models, low student engagement, and teacher-dominated learning activities are the root causes of this problem. A model that has been used to address this issue is the Think Talk Write (TTW) cooperative learning model. The primary objective of this study is to determine whether the TTW model yields superior learning outcomes compared to conventional instruction and to characterize the progress integrated by the TTW model. A nonequivalent posttest-only control group design was employed, making this a quasi-experimental study. Grade VIII-4 and VIII-5 at SMPN 7 Padang served as the study sample. Quizzes and final exams were used to collect data for this study. The t-test results showed that p-value = 0.001, rejecting H0. Therefore, it can be concluded that compared to the conventional learning model, the learning outcomes in mathematics using the TTW model are significantly better.